Photovoltaics: New Policy Challenges for Europe - De Sousa, Luís A. (Frontiers in Energy Research, 2013)
After the turn of the century governments across Europe set in place a series of programmes to expand investment on grid-connected solar power technology, especially photovoltaics (PV). But in face of rapidly declining costs most of these programmes have been tapered in recent months. Using a simple cost model this article shows that PV technologies can indeed supply electricity to the grid for less than 0.10 €/kWh in large swaths of the continent, apparently justifying this policy change. However, the roll back of fixed rates to PV suppliers will likely result in a market structure close to perfect competition, where profits are not expectable and the price should fall towards marginal generation cost: 0 €/kWh. Due to the scalable nature of PV, many consumers in Europe are now able to produce their own electricity at a cost considerably lower than the rates demanded by grid utilities. Investment on PV is thus set to continue in spite of recent policy changes, but henceforth on off-the-grid systems, conceived for self consumption. Long term this trend presents serious challenges to utilities and traditional electricity suppliers, putting at stake the existing electricity market framework.